Steroid‐free and steroid withdrawal protocols in heart transplantation: the review of literature. (12th April 2014) - Baraldo, Massimo; Gregoraci, Giorgia; Livi, Ugolino
Summary Corticosteroids (CSs) are still the mainstay of induction, rescue, and maintenance in heart transplantation (HTx). However, their use is associated with significant and well‐documented side effects usually related to the dose administered and the duration of therapy. Moreover, CSs interfere with the recipient's quality of life and with the active process of graft tolerance. Physicians have been exploring ways to avoid or reduce CSs in association with other immunosuppressive drugs, minimizing side effects and costs. The regimens are classified as steroid‐free or steroid withdrawal protocols. The studies analyzed in this review come to similar conclusions as benefits and adverse consequences: steroid‐free protocols should be advisable and mandatory in pediatric patients, insulin‐dependent diabetes mellitus (IDDM), presence of infection, familial metabolic disorders/obesity, severe osteoporosis, and in the elderly. On the other hand, steroid withdrawal can be successfully achieved in 50–80%, with late better than early withdrawal, no increase in rejection‐related mortality, no adverse impact on survival, and probably a better quality of live. Safety and efficacy can certainly be improved by an individualized approach to the transplant recipient.